Republic of Poland : Arrangement Under the Flexible Credit Line and Cancellation of the Current Arrangement-Press Release; Staff Report; and Statement by the Executive Director and Alternate Executive Director for the Republic of Poland. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Poland's Arrangement Under the Flexible Credit Line (FCL) and Cancellation of the Current Arrangement. The FCL arrangements since 2009 have served Poland well, providing valuable insurance against external shocks. With the support of the consecutive FCL arrangements, Poland has weathered bouts of market turbulence well, and remains an attractive investment destination. The authorities intend to continue treating the FCL as precautionary and consider it a temporary supplement to reserves. In IMF staff's view, Poland continues to meet the qualification criteria for continued access to the FCL.